2017
DOI: 10.1111/nph.14674
|View full text |Cite
|
Sign up to set email alerts
|

How functional is a trait? Phosphorus mobilization through root exudates differs little between Carex species with and without specialized dauciform roots

Abstract: Root structures secreting carboxylates and phosphatases are thought to enhance a plant's phosphorus (P) acquisition. But do closely related species with and without such structures really differ in root exudation, P mobilization, or ecological niche? We investigated this by comparing 23 European Carex species with and without 'dauciform roots' (DRs). Plants grown in pots with sand were screened for DR formation, phosphatase activities, carboxylate exudation, and utilization of various organic and inorganic P c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 81 publications
3
29
0
Order By: Relevance
“…However, as the size of the geometry, l, increases assuming the reactions are in equilibrium becomes more appropriate. In contrast, previous experiments are in agreement with the current finding, both Güsewell and Schroth (2017) and Ryan et al (2014) could not detect P uptake gains in high carboxylate exuding plants in comparison to low carboxylate exuding subgenus/near-isogenic species.…”
Section: Microdialysis Probes As Root Analoguessupporting
confidence: 91%
“…However, as the size of the geometry, l, increases assuming the reactions are in equilibrium becomes more appropriate. In contrast, previous experiments are in agreement with the current finding, both Güsewell and Schroth (2017) and Ryan et al (2014) could not detect P uptake gains in high carboxylate exuding plants in comparison to low carboxylate exuding subgenus/near-isogenic species.…”
Section: Microdialysis Probes As Root Analoguessupporting
confidence: 91%
“…Any decline in A area with declining LMA was offset by a disproportionate increase in A mass that slowed the decrease in PNUE relative to the decline in photosynthetic capacity. The scaling relationships of R dark,area and R dark,mass on N area had similar countervailing effects, which were consistent with the respiratory costs of dauciform roots specialized for P uptake in Carex (Güsewell & Schroth, ), as both R dark,area and R dark,mass were associated with increasing P mass . Finally, the shade‐induced decline in LMA was also associated with a disproportionate reduction in P area and corresponding increases in the N : P ratio and growth.…”
Section: Discussionsupporting
confidence: 78%
“…We evaluated changes in the scaling relationships between the LES traits and net production over the course of the experiment (hereafter ‘GROWTH’) for plants grown in regimes differing in above‐ground (shaded vs unshaded) and below‐ground (insufficient vs sufficient P) resource availability. We chose P as a potentially limiting resource because of the influence of P‐availability on global patterns of variation in foliar traits (Maire et al ., ), the functional significance of the N : P ratio (Güsewell, ), the possible role of the N : P ratio in affecting growth (Yu et al ., ; Yan et al ., ), and the specialized mechanisms Carex species have for P uptake (Güsewell & Schroth, ). Additionally, the role of foliar P in the LES is poorly understood compared with the role of foliar N (Crous et al ., ; Onoda et al ., ; Onoda & Wright, ).…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, it has been documented that RA‐Phy activity was less than 1% of total RA‐APase activity in plants, such as Arabidopsis, wheat, and Carex species (Güsewell & Schroth, ; Richardson et al, ; Richardson, Hadobas, & Hayes, ), although RI‐Phy activity could account for about 0.5–5% of total RI‐APase activity in plants (Araújo, Plassard, & Drevon, ; Lung & Lim, ; Richardson et al, ; Sharma & Sahi, ). However, it was observed that RA‐Phy activity accounts for 2.3–3.8% of RA‐APase activity among the tested 39 stylo genotypes (Figures S1 and S2).…”
Section: Discussionmentioning
confidence: 65%